CORRELATION OF STUDENT PERCEPTIONS ON LEARNING ENVIRONMENT, PARTICIPATION, AND ACADEMIC PERFORMANCE IN A MEDICAL SCHOOL - Yusril Rahmi Sukmawati; Dian Puspita Sari; Yoga Pamungkas Susani (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2019)
Background: Student perceptions of the learning environment can influence student participation in learning. Both of these variables can possibly affect students’ academic performance. The purpose of this study was to assess the correlation between perceptions of the learning environment, participation in PBL tutorials, and academic performance of the pre-clinical stage students of the Faculty of Medicine Universitas Mataram.Methods: This was a cross-sectional study. Student perceptions of the learning environment were assessed using The Dundee Ready Education Environment Measure (DREEM) questionnaire. Participation in PBL tutorials was measured by an instrument that assess preparation for the tutorial, interactions during the tutorial, and students’ self-management. Academic performance was measured from the block’s main exam score. A total of 286 out of 303 medical students from year 1 to year 4 (94.39%) participated in this study.Results: The mean of the total DREEM score, participation score, and academic performance respectively were135.94 ± 17.27; 83.20 ± 9.48; and 61.48 ± 13.47. There was a correlation between student participation and academic performance (r 0.569, p < 0.001), student perceptions of the learning environment and student participation (r = 0.225, p < 0.001), and student perceptions of the learning environment and academic performance (r = 0.190, p < 0.001).Conclusion: Student participation in tutorials is related to student academic performance. Participation possibly mediates the relationship between student perceptions of the learning environment and academic performance.